Tolerance of Continuous Positive Airway Pressure After Sinonasal Surgery. (16th September 2020) - Reilly, Erin K.; Boon, Maurits S.; Vimawala, Swar; Chitguppi, Chandala; Patel, Jena; Murphy, Kira; Doghramji, Karl; Nyquist, Gurston G.; Rosen, Marc R.; Rabinowitz, Mindy R.; Huntley, Colin T.
Abstract : Objectives/Hypothesis: For patients with obstructive sleep apnea (OSA) undergoing sinonasal surgery, there is a lack of consensus on the risk and appropriate postoperative use of continuous positive airway pressure (CPAP). The aim of this study was to assess the tolerability of restarting CPAP on postoperative day one. Study Design: Prospective cohort study. Methods: A prospective study on patients with OSA on CPAP who required a septoplasty/turbinectomy and/or functional endoscopic sinus surgery (FESS) was performed. Data from the memory card of a patient's CPAP machine and subjective information were obtained on the day of surgery and at scheduled follow‐up visits. All subjects were instructed to restart CPAP on the first postoperative night. Results: A total of 14 patients were analyzed; nine underwent FESS and five had a septoplasty/turbinectomy. There were no postoperative complications encountered. The only significant change in the first postoperative week was a reduction in the percentage of nights used over 4 hours ( P < .05). By the third postoperative visit, average 22‐item Sino‐Nasal Outcome Test, Nasal Obstruction Symptom Evaluation, and CPAP tolerance scores improved from preoperative values. CPAP pressures, residual apnea–hypopnea index, and number of hours and mean percentage of nights used remained stable throughout the study period. Conclusions: Both quality‐of‐life and CPAP outcomes improved or remained the same when restarting CPAP immediately postoperatively. Combined with a lack of significant complications, this study suggests that CPAP is well‐tolerated when restarted the day after a septoplasty/turbinectomy or FESS. Level of Evidence: 4 Laryngoscope, 131:E1013–E1018, 2021